Prevalence of Breast Feeding in the Locality of IBN- Al- Baldy Hospital - Hasan Dhary Al-Jumaily, Ali (Tikrit Journal of Pharmaceutical Sciences, 2023)
One hundred mothers of children below two years of age were interviewed regarding some socioeconomic and health factors affecting breast-feeding in the area seived by IBN-AL-balady Hospital in Baghdad at august 200?. The study revealed that 57Yo of the mothers were exclusively breast-feeding their children insufficient milk was the most common mentioned reason (57.7%) for starting bottle feeding.A negative association was observed between breast -feeding and education of the mothers" Illiterate mothers were more likely to breast;-feed their infants (70%) than educated mothers (57.1 %) .More governmental and social support is needed to promote and protect breast feeding in our society.